Pengaruh Brand Image dan Persepsi Harga terhadap Keputusan Pembelian Produk Kosmetik Make Over pada Generasi Z di Kota Tegal - Fanny Erlianti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The rapid growth of Indonesia's cosmetics industry has intensified competition among local brands and increased the need to understand Generation Z purchasing behavior. This study analyzes the influence of brand image and price perception on purchasing decisions for Make Over cosmetic products among Generation Z consumers in Tegal City. The study used a quantitative approach with a cross-sectional survey design. Data were collected through questionnaires from 100 female respondents aged 15-29 years who lived in Tegal City and had purchased or used Make Over products. Respondents were selected using purposive sampling. The research instrument consisted of 18 Likert-scale statements covering corporate image, product image, user image, price affordability, price-quality suitability, price-benefit suitability, product choice, brand choice, and purchase amount. Data were analyzed using multiple linear regression with SPSS version 26 after validity, reliability, normality, multicollinearity, heteroscedasticity, and linearity tests. The results show that brand image has no significant partial effect on purchasing decisions, with t = 0.279 and p = 0.781. Price perception has a positive and significant effect, with t = 5.417 and p < 0.001. Simultaneously, brand image and price perception significantly affect purchasing decisions, with F = 21.288 and p < 0.001. The adjusted R Square of 0.291 indicates that both variables explain 29.1% of purchasing decision variation. These findings show that respondents value Make Over's reputation and quality, but purchasing decisions depend more strongly on affordability and perceived value. Therefore, Make Over should maintain brand communication and strengthen value-based pricing strategies aligned with Generation Z needs